7(4x+6)+11=

Simple and best practice solution for 7(4x+6)+11= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(4x+6)+11= equation:


Simplifying
7(4x + 6) + 11 = 0

Reorder the terms:
7(6 + 4x) + 11 = 0
(6 * 7 + 4x * 7) + 11 = 0
(42 + 28x) + 11 = 0

Reorder the terms:
42 + 11 + 28x = 0

Combine like terms: 42 + 11 = 53
53 + 28x = 0

Solving
53 + 28x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-53' to each side of the equation.
53 + -53 + 28x = 0 + -53

Combine like terms: 53 + -53 = 0
0 + 28x = 0 + -53
28x = 0 + -53

Combine like terms: 0 + -53 = -53
28x = -53

Divide each side by '28'.
x = -1.892857143

Simplifying
x = -1.892857143

See similar equations:

| 42a-22=-4(1-6a) | | -7*-7=x | | 7(4c+6)+11= | | 12x-1=6x+16 | | 3(x^2-1)=8x | | -3-4y=17 | | -4-18=-2(u-6) | | -x-89=177-8x | | 4(v-8)-8v=-28 | | 3y-10=y+30 | | y=12(0.85)x | | -2/3x-9/7=-1/2 | | -3x(2x+5)=-4(-x+2) | | 11x+3-5x= | | -x(13+4x)=-3(5-9x)+2 | | (7x+2)+(18-7x)= | | r^3+4r^2=0 | | -115+x=9x+93 | | 5(2-x)+10x-8=27 | | x^2-10x=e^2 | | (6+5)8=N+40 | | 6(4x+6)+3x= | | 2(x)-3=5 | | y=x^2-4+2 | | (16x-7)+(12-2x)= | | 3ln(8x)=24 | | (6x+15)+10= | | x^3-7x^2+8x=0 | | 11x-16=12x+9 | | 6(5x+5)+6x= | | h-(h*h)=0.18 | | 11(3x+9)-12x= |

Equations solver categories